3‐Chlorooxindoles: Versatile Starting Materials for Asymmetric Organocatalytic Synthesis of Spirooxindoles. Issue 5 (15th March 2013) - Noole, Artur; Ošeka, Maksim; Pehk, Tõnis; Öeren, Mario; Järving, Ivar; Elsegood, Mark R. J.; Malkov, Andrei V.; Lopp, Margus; Kanger, Tõnis
Abstract 3‐Chlorooxoindoles have emerged as versatile precursors in the synthesis of spirocyclopropyl oxindoles. High enantio‐ and diastereoselectivity was attained under conditions of both iminium/enamine and H‐bonding catalysis.